Cardiac resynchronization considerations in left bundle branch block - Kong, Nathan W.; Upadhyay, Gaurav A. (Frontiers in Physiology, 2022)
Cardiac resynchronization therapy (CRT) via biventricular pacing (BiVP) is an established treatment for patients with left ventricular systolic heart failure and intraventricular conduction delay resulting in wide QRS. Seminal trials demonstrating mortality benefit from CRT were conducted in patients with wide left bundle branch block (LBBB) pattern on electrocardiogram (ECG) and evidence of clinical heart failure. The presence of conduction block was assumed to correlate with commonly applied criteria for LBBB. More recent data has challenged this assertion, revealing that LBBB pattern may include distinct underlying pathophysiology, including patients with complete conduction block, either at the left-sided His fibers or the proximal left bundle, intact Purkinje activation with wide LBBB-like QRS, and patients demonstrating both proximal block and distal delay. Currently, BiVP-CRT is indicated for all QRS duration ≥150 ms and may be considered for BBB patterns from 130-149 ms with robust clinical data to support its use. Despite this, however, there remains a significant number of non-responders to BVP. Conduction system pacing (CSP) has emerged as an alternative approach to deliver CRT and correct QRS in patients with conduction block. Newer hybrid approaches which combine CSP and traditional BiVP-CRT and may hold promise for patients with IP or mixed-level block. As various approaches to CRT continue to be studied, physiologic phenotyping of the LBBB pattern remains an important consideration.